Synthesis of highly c-oriented ZIF-69 membranes by secondary growth and their gas permeation properties - Liu, Yunyang; Zeng, Gaofeng; Pan, Yichang; Lai, Zhiping (Journal of membrane science, 2011)
► A secondary growth process was developed to synthesize highly c-oriented ZIF-69 membranes. ► Improved membrane microstructure, particularly degree of the membrane orientation was achieved. ► Improved membrane performances in both permeability and selectivity were achieved. ► A facile synthesis method was developed to make ZIF-69 particles down to sub-micrometers. A seeded growth procedure was successfully developed to synthesize highly c-oriented and well-intergrown zeolitic imidazolate framework-69 (ZIF-69) membranes on porous α-alumina substrates. The synthesis conditions were optimized both for seed preparation and for secondary growth. For seeding, a facile method was developed to prepare smaller and flat ZIF-69 microcrystals in order to make thin and c-oriented seed layers. While for secondary growth, a synthesis condition that favored the growth along the c-direction was chosen in order to form highly c-oriented ZIF-69 membranes after growth. As a result, the majority of ZIF-69 grains inside the membrane have their straight channels along the crystallographic c-axis aligned perpendicularly to the substrate surface. Such alignment was confirmed by both XRD and pole figure analysis. The mixture-gas separation studies that were carried out at room temperature and 1 atm gave separation factors of 6.3, 5.0, 4.6 for CO 2/N 2, CO 2/CO and CO 2/CH 4 respectively, and a permeance of ∼1.0 × 10 −7 mol m −2 s −1 Pa −1 for CO 2 in almost all mixtures. Both the separation factor and permeance were better than the performance of the ZIF-69 membranes prepared by the in situ solvothermal method due to improvement in the membrane microstructure by the seeded growth method.